The Antithetical Dualities in Omar bin Abi Rabi’ah’s Poetry - Abdel, Omar Mahmoud (Journal of Tikrit University for Humanities, 2025)
The concept of antithesis or dichotomy in poetic texts is founded on complex and parallel motivations and contexts, eventually forming a linguistic structure that translates the poet’s ideas, psyche, and inner composition based on a critical or emotional philosophical idea, manifesting in literature in general and poetry in particular. This research is a new reading of the poet Omar bin Abi Rabi’ah’s work, delving into the linguistic and poetic structure of his texts and uncovering symbolic meanings through antithesis, while exploring the psychological dimensions of the antithesis presented in this research, which we attempted to follow in the poet’s work and evaluate its effectiveness in the texts. Since antithesis is present as long as humans exist, such as life and death, and existence and non-existence, we followed the path of antithesis in the poet’s collection and identified three distinct sections. The first section deals with the antithesis of closeness and distance, and the potential psychological and emotional conflict it may evoke in the poet. The second section discusses the antithesis of separation and union, explored through the theme of women and its resulting psychological and emotional dimensions. The third section is devoted to the poet’s emotional and sensory adventures. We observed the effectiveness of antithesis in Omar bin Abi Rabi’ah’s poetry and the poetic and aesthetic characteristics he added to his literary texts, and we assessed the extent of the poet’s success in utilizing these antitheses.